THE TRAUMATIC CONFRONTATION WITH IDEOLOGY AND THE REAL IN E.L.DOCTOROW’S "WELCOME TO HARD TIMES": : A ŽIŽEKIAN STUDY - Borzabadi Farahani, Hojatallah; Beyad, Maryam (Gênero & Direito, 2020)
Social reality in its essence is political, and any exploration of it needs a political performance. Concerning the issue, literature, by and large, has gained a political function through history. It has been an efficient political device to represent the role and the impact of ideology on the way of living and identity of people. E. L. Doctorow’s novels in general, and his Welcome To Hard Times in particular approve of the author’s interest in the ideological constitution of American society and the inevitable confrontation of the people with the intrusion of the Real [a Žižekian term] and the regressive work of ideology. In the light of Žižekian perception of the word, ideology is a form of socio-political philosophy in which practical elements are as prominent and decisive as theoretical ones. To him, ideology is a set of ideas licensing social actions and allocating subjects predetermined Symbolic Orders within the context of elusive reality. It gives them a social mandate, and a specific identity to deal with the worldly affairs. However, in Doctorow’s Welcome to Hard Times we come to a community of figures, marginal though, who take a rebellion action against ideology to alter the given identity employing their [personal] acts. The present study aims at exploring this reformative attempt on part of the people involved in ideological restrictions.